Comparative analysis of the probability of use of family planning methods in women from 12 to 49 years in 2006 and 2014 (Horizontes de Enfermería, 2018)
This paper presents a comparative analysis of the probability of using family planning methods in women aged 12 to 49 years in 2006 and 2014, based on information from the family planning module in the Living Conditions Survey. For this, a methodological test was developed, which allowed comparing the results at the level of representativeness and area. From this, a logistic model of probability that allows to evaluate the variation in the probability obtained for the 2 years. It is important to note that the results are statistically different, however, changes in probability show an increase in the use of family planning methods, given by factors such as work, age, marital status, among others.
Keywords: survey; family planning; probability; representativity; factors; contraceptives